Local tourism in the city of Barcelona: motivating and rejecting factors of a sustainable tourism model - Gutiérrez-Aragón, Óscar; Puiggròs-Román, Elena; Fondevila-Gascón, Joan-Francesc; Duran-Moreno, Alba (Scripta Mundi, 2025)
Since the 1992 Olympic Games, the Barcelona’s popularity, supply and demand for tourism have grown exponentially, turning the city into a destination whose sustainable management is increasingly complicated (overtourism). The objective of this research is to analyze the potential that local tourism would have for Barcelona as a medium-term bet in oder to create a more sustainable tourism model, as well as to know the main factors that motivate or reject this type of tourism. A methodological combination of quantitative analysis has been used, both from official secondary sources and from data from a survey (primary source) carried out on residents of Catalonia, in their capacity as potential local tourists. The results reveal that 83.6% of the participants in the study recognize the realization or interest in visiting places close to their residence and that the main factors that determine the decision to visit Barcelona are, in general, the price of the visit and the available time. Furthermore, as the level of education is higher, a greater degree of motivation is shown towards the practice of local tourism if more information is available about the places to visit or if those places do not show signs of tourist overcrowding. It is concluded that local tourism would be an alternative to be explored by companies in the sector and tourism management institutions in the city, since an active predisposition is detected in the target audience to visit the city, mainly those less congested tourist resources